2023
DOI: 10.1021/acssuschemeng.3c01912
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Cobalt-Catalyzed Coupling of Amines and Siloxanes to Prepare Ceramics and Polymers

Abstract: The phosphine-substituted aryl diimine cobalt catalyst, ( Ph2PPr ADI)Co, has been found to mediate the dehydrocoupling of diamines or polyamines to poly(methylhydrosiloxane) (PMHS) to generate hydrogen and crosslinked solids in an atom-efficient fashion. The resulting siloxane diamine and siloxane polyamine networks persist in the presence of air or water at room temperature and can tolerate temperatures of up to 1600 °C. Upon lowering the catalyst loading to 0.01 mol %, ( Ph2PPr ADI)Co was found to catalyze t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Products 1a and 2a , which feature ethylenediamine linkers, were observed to hydrolyse considerably faster than the networks featuring longer chain diamines, which impart greater hydrophobicity. 19…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Products 1a and 2a , which feature ethylenediamine linkers, were observed to hydrolyse considerably faster than the networks featuring longer chain diamines, which impart greater hydrophobicity. 19…”
Section: Resultsmentioning
confidence: 99%
“…18 Our group subsequently demonstrated that the aryl diimine (ADI) cobalt catalyst, ( Ph2PPr ADI)Co, can dehydrocouple diamines and hydrosiloxanes with turnover frequencies (TOFs) of up to 157 s −1 relative to substrate. 19 Prior to this study, the highest activity for Si-N dehydrocoupling was 91.7 s −1 , reported for the N-heterocyclic carbene complex, [Pt(I t Bu′)(I t Bu)][BAr F 4 ]. 13,20 In 2018, our group reported the synthesis of the manganese hydride dimer, [( 2,6-iPr2Ph BDI)Mn(µ-H)] 2 (1, Fig.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations